Students’ learning obstacle in operations of integer - Kurniasi, Rima; Nurjanah, Nurjanah; Cahya, Endang (ARKA INSTITUTE, 2024)
This study aims to describe the learning obstacles faced by students in the operation of integers. The research method used is a qualitative method with a case study design. The data was taken from 16 students in grade 7, a junior high school in Batang Hari, Jambi. The data collection technique used was triangulation data. There are written tests, interviews with both students and the teacher, and document analysis. The data collection instrument used was a test of integer operations, interview guidelines, and documents (lesson plan and textbook). The results of the research showed that there are learning obstacles in the operations of integers, namely, ontogenic obstacles (difference in knowledge between natural number operations and integer operations), epistemological obstacles (limited understanding), and didactical obstacles (obstacles that come from the didactic system). Other researchers can create lesson plans based on the obstacles found in this research.